(untitled) (Indo-MathEdu Intellectuals Journal, 2023)
Project-based learning emphasizes assigning tasks or projects that involve children in research, planning, and execution. This study aims to determine the use of loose part teaching materials through a project-based learning model to stimulate early childhood creativity in Baitul Ilmi Kindergarten. This research uses a qualitative approach with a case study method. The data collection techniques used are observation and interviews. Research data analysis is carried out qualitatively consisting of data reduction, data presentation and conclusions. The results of data analysis show that the use of loose parts teaching materials through project-based learning models has a positive impact on improving creativity and memory in early childhood. The results of observations, interviews, and case studies in group A showed that children not only expressed their creativity through the selection and use of teaching materials, but also experienced improvements in creative collaboration and team involvement during project activities. In addition, sensory experiences, especially involving the scent of suji leaves and pandan leaves, help strengthen children’s memory. The practical implications of this research include developing a curriculum that is more contextual and involves loose parts teaching materials in learning strategies.